Optimizing Activators Regenerated by Electron Transfer for Atom Transfer Radical Polymerization of Methyl Methacrylate Initiated by Ethyl 2-bromopropionate - Chen, Mingsen; Zhou, Hongwang; Li, Xiaofang; Zhou, Li; Zhang, Faai (Journal of Research Updates in Polymer Science, 2016)
In this study, we used ethyl 2-bromopropionate (EBrP) as an initiator of activators regenerated by electron transfer for atom transfer radical polymerization (ARGET ATRP) of methyl methacrylate (MMA). We investigated in detail the effect on polymerization of different kinds of reducing agents and ligands, the amounts of the reducing agent and catalyst, and reaction temperature. We determined the molecular weight and dispersity of the polymers by gel permeation chromatography (GPC). The results reveal glucose to be the best reducing agent for this system. The monomer conversion increased with increases in the reaction temperature and in the feeding amounts of the reducing agent and catalyst. The optimum amount of the reducing agent and minimal amount of catalyst required depend on the particular system. For example, we polymerized MMA with 200 ppm of catalyst and 15-fold of glucose/CuCl2 resulting in a PMMA with high Mn (Mn,GPC = 48 700, Mn,theo = 48 500) and low dispersity (1.27). The first-order kinetics show that the molecular weights increased linearly with the monomer conversion and are consistent with the theoretical values, the chain extension reaction and end group analysis results also demonstrate that the characteristics of polymerization process belong to a typical “living”/controlled radical polymerization. Moreover, 1H-NMR analysis results indicate the stereoregularity of the polymer is given priority over syndiotactic architecture and the effect of the type of ligand on the stereoregularity is very slight.